L∞-Estimates of the Bergman projection in the Lie ball of ℂn - Cyrille Nana (Journal of Function Spaces and Applications)
In this paper, we consider estimates with loss for the Bergman projections of bounded symmetric domains of ℂn in their Harish-Chandra realizations. This paper is twofold: on one side we develop transfer methods between these bounded domains and their Cayley transform; on the other side we give a new range of q such that the Bergman projection is bounded from L∞(ℬn) to Lq(ℬn) where ℬn is the Lie ball of ℂn.